Strengthened multi-stakeholder linkages in valuation studies is critical for improved decision making outcomes for valuable mangroves – The Malaysian case study - Lee, Soon Loong; Then, Amy Yee-Hui; Goh, Hong Ching; Hattam, Caroline; Edwards-Jones, Andrew; Austen, Melanie C. (Frontiers in Marine Science, 2022)
Mangrove forests in Southeast Asia are continuously declining as a result of unsustainable practices, partly due to limited recognition of the value of mangrove services in land use decision making. Valuation practitioners have assumed that monetary valuation should inform local and national decision makers to ensure sustainable management of mangrove resources. For ecosystem service valuation to be of use to decision makers, best practices should be adhered to such as having straightforward policy questions and strong stakeholder engagement from the onset of valuation studies, suitable choice of valuation methodologies, and the ability to effectively demonstrate causal links between drivers of ecosystem health, change, and resource users. This study, focusing on the Malaysian case study, assessed the effectiveness and challenges of local ecosystem service valuation studies in informing mangrove management decisions against a set of global best practices. A systematic review approach was undertaken to identify relevant Malaysian mangrove ecosystem service valuation studies. Of 184 studies identified, only 17 provided monetary values for mangrove ecosystem services. These studies valued nine different mangrove ecosystem services, with the cultural ecosystem services of tourism being the most frequently valued. Most of the valuation studies were designed to raise awareness of the value of ecosystems (64.7%). Other intended uses included determining appropriate charging rates for mangrove uses (17.6%), comparing the costs and benefits of different environmental uses (11.8%), and providing a justification and support for certain decision making (5.9%). Overall, mangrove valuation studies in Malaysia were characterized by weak multi-stakeholder engagement, non-standardized valuation units across the whole country, limited dissemination of the valuation outcome, and cursory references to the potential use of mangrove ecosystem services. Most of the studies did not exert apparent influence on mangrove management. Future valuation studies in Malaysia and the Southeast Asian region should aim to build more robust engagement between valuation practitioners and key stakeholder groups, especially decision makers, at all stages of the study process and incorporate a clear dissemination strategy for sharing results.